Will Exercise Advice Be Sufficient for Treatment of Young Adults With Prehypertension and Hypertension? A Systematic Review and Meta-Analysis. Issue 1 (July 2016) - Williamson, Wilby; Foster, Charlie; Reid, Hamish; Kelly, Paul; Lewandowski, Adam James; Boardman, Henry; Roberts, Nia; McCartney, David; Huckstep, Odaro; Newton, Julia; Dawes, Helen; Gerry, Stephen; et al.
Abstract : Previous studies report benefits of exercise for blood pressure control in middle age and older adults, but longer-term effectiveness in younger adults is not well established. We performed a systematic review and meta-analysis of published randomized control trials with meta-regression of potential effect modifiers. An information specialist completed a comprehensive search of available data sources, including studies published up to June 2015. Authors applied strict inclusion and exclusion criteria to screen 9524 titles. Eligible studies recruited younger adults with a cardiovascular risk factor (with at least 25% of cohort aged 18–40 years); the intervention had a defined physical activity strategy and reported blood pressure as primary or secondary outcome. Meta-analysis included 14 studies randomizing 3614 participants, mean age 42.2±6.3 (SD) years. At 3 to 6 months, exercise was associated with a reduction in systolic blood pressure of −4.40 mm Hg (95% confidence interval, −5.78 to −3.01) and in diastolic blood pressure of −4.17 mm Hg (95% confidence interval, −5.42 to −2.93). Intervention effect was not significantly influenced by baseline blood pressure, body weight, or subsequent weight loss. Observed intervention effect was lost after 12 months of follow-up with no reported benefit over control, mean difference in systolic blood pressure −1.02 mm Hg (95% confidence interval, −2.34 to 0.29), and in diastolic blood pressure −0.91 mm Hg (95% confidence interval, −1.85 to 0.02). Current exercise guidance provided to reduce blood pressure in younger adults is unlikely to benefit long-term cardiovascular risk. There is need for continued research to improve age-specific strategies and recommendations for hypertension prevention and management in young adults. Abstract : Supplemental Digital Content is available in the text.